SHIFTING INTERPRETATION OF JOHN KERRYS SPEECH ABOUT SYRIA CONFLICT REPORTED BY KOMPAS TV - Sheellviana Dewi; Dian Rivia Himmawati (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
The issue of John Kerrys speech about Syria conflict reported by Kompas TV takes interpretation process. Interpretation used in transforming source language (John Kerry/English) to target language (Kompas TV/Indonesian). The aim of this study is revealing shifting interpretation inserted by Kompas TV while reporting John Kerrys speech about Syria conflict. Documentary video from Kompas TV and the United States official channel on YouTube is the data which consist of three videos. Qualitative data approach is applied to this study because the analysis gives explanation to strength the findings. The result of the analysis shows that Kompas TV used complex syntax, making long passage into a sentence, de-verbalization, and compression to get John Kerrys idea. All of John Kerrys utterances are simplified into the simple one. Hence, Kompas TV shifts the interpretation through complex syntax process which  is inserted in semantic macrostructures, syntactic of subject position, self-define of terrorist, and disclaimer to reject racism.